Educational Services Marketing Strategy in Increasing the Interest of Prospective Education Candidates - Tyas, Hifani Nimas; Sultoni, Sultoni; Sunandar, Asep (Universitas Negeri Malang, 2024)
This article discusses the marketing mix of educational services and its application in increasing the interest of prospective students in educational institutions. Using the literature study research method, an analysis was carried out on the elements of the marketing mix, namely products, prices, places, people, facilities, processes, and promotions, as well as how each element contributes to attracting prospective students. The findings show that relevant and quality program offerings, competitive pricing, and accessibility of educational locations are key factors in attracting interest. Additionally, the use of innovative promotional strategies, including digital marketing and engagement with the community, can significantly strengthen the institution's image. This article provides insight into the importance of integrating marketing strategies in the context of education, as well as recommendations for institution managers to optimize the marketing mix to increase the enrollment of prospective students effectively and sustainably, ensuring the institution's long-term success.